The irony of privatization - Miller, Hugh T.; Simmons, James R. (1998)
What does privatization really mean? It depends on who is speaking and the specific language game in use. This article borrows an interpretive device, originally developed by Roland Barthes and further articulated by Jean Boudrillard, which lays waste to the assertion that a word has a single denotative meaning. Such an interpretation (that words represent, or correspond to, reality) is but the first step of a progressively unreal simulacrum that moves to skepticism, through masking (where a word connotes the radical absence of the object it points toward) to hyperreality. Hyperreality is the domain of self-referential imagery, where words and symbols refer only to themselves but provide titillation and visceral gratification in the process. The authors conclude that the very term privatization lacks foundational stability. - Reproduced
Keywords: Privatization